Forest politics the evolution of international cooperation - Humphreys, David (London Earthscan, 2009)
Forest Politics carefully traces the evolution of international cooperation on forests, from the inception of the controversial International Tropical Timber Organization and the failed Tropical Forestry Action Programme in the mid-1980s, to the creation of the Intergovernmental Panel on Forests in the mid-1990s. The book also provides a detailed analysis of the negotiating stances of the parties involved in the divisive negotiations that rook place prior to the 1992 Earth Summit in Rio de Janeiro and the equally factious negotiations for the International Tropical Timber Agreement of 1994. It provides a fascinating insight into the nature of such processes, illustrating the difficulties that arise when concepts such as 'global commons' come into conflict with national sovereignty.
"Earthscan publishes in association with the International Institute for Environment and Development."
Keywords: Forest conservation -Political aspects -History.